(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
A Spiritual Literary Perspective of the Life of the Classic Nicolae Gogol. The purpose of this research is to show the multilateral nature of the life of the Ukrainian-Russian classic Nicolae Gogol, namely the literary, theological and historical wealth that the literary giant uses in the creation of national and international literary works. From the present research it will become clear that Gogol’s life, on the one hand, brings to the reader’s attention the wide range of scriptural principles and teachings that were transposed and introduced into the life of the characters, into the life of the country (Ukraine and Russia) and into the correspondence of the classic Russian. On the other hand, the reader will arrive at the answer to the question: why Gogol introduced into his works biblical truths, patristic works and theological teachings, which, by the way, are primary for a Christian life.